2018
DOI: 10.3171/2017.7.spine161327
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, randomized, double-blind, dose-finding study of condoliase in patients with lumbar disc herniation

Abstract: OBJECTIVEChemonucleolysis with condoliase has the potential to be a new, less invasive therapeutic option for patients with lumbar disc herniation (LDH). The aim of the present study was to determine the most suitable therapeutic dose of condoliase.METHODSPatients between 20 and 70 years of age with unilateral leg pain, positive findings on the straight leg raise test, and LDH were recruited. All eligible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 25 publications
(24 reference statements)
1
61
0
Order By: Relevance
“…Specifically, C-ABC has been previously evaluated for its therapeutic potential to degrade tissue fragments impinging on nerves in patients with herniated IVDs. (45) The administration of C-ABC enzyme initiates the targeted degradation of NP tissue to provide an accelerated degeneration cascade similar to conditions observed in humans as a result of increased levels of matrix metalloproteinases (MMPs) and a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) observed within increasing levels of IVDD; thus, intradiscal injection of C-ABC has been used as a method of initiating IVDD in large animals to serve as models for studying pathological mechanisms and preclinical assessments of potential therapeutics. (21), (22), (29), (30) .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, C-ABC has been previously evaluated for its therapeutic potential to degrade tissue fragments impinging on nerves in patients with herniated IVDs. (45) The administration of C-ABC enzyme initiates the targeted degradation of NP tissue to provide an accelerated degeneration cascade similar to conditions observed in humans as a result of increased levels of matrix metalloproteinases (MMPs) and a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) observed within increasing levels of IVDD; thus, intradiscal injection of C-ABC has been used as a method of initiating IVDD in large animals to serve as models for studying pathological mechanisms and preclinical assessments of potential therapeutics. (21), (22), (29), (30) .…”
Section: Discussionmentioning
confidence: 99%
“…Chymopapain was introduced in July 1963 and was widely used throughout Europe, North America, and Australia [8][9][10]. Following reports of severe adverse events, including fatal anaphylaxis, bleeding, and neurologic complications [11][12][13][14][15][16], the production of chymopapain (Chymodiactin® , Smith Laboratories Inc., MN, USA) was discontinued for nonscientific and commercial reasons in 2002. The first clinical study on collagenase (nucleolysin) was reported in 1981 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Phase 1-3 clinical trials of condoliase were conducted in Japan. Matsuyama et al reported the results of phases 2 and 3 trials of chemonucleolysis for the treatment of LDH (Clinical trial registration no.NCT00634946) [11]. In this study, 194 patients received three different doses of condoliase (1.25, 2.5, or 5 U) or placebo injections, and the appropriate dose of injection was determined (1.25 U).…”
Section: Introductionmentioning
confidence: 99%
“…The JOA score had improved to 21/29 points. Condoliase injected into an intervertebral disc specifically dissolves glycosaminoglycans, which constitute proteoglycans, the main component of the nucleus pulposus 6) . This restricts the proteoglycans' water-holding capacity, reducing pressure inside the intervertebral disc, lowering the pressure on the nerve root from the hernia, and improving lower extremity and low back pain 6) .…”
mentioning
confidence: 99%
“…Condoliase injected into an intervertebral disc specifically dissolves glycosaminoglycans, which constitute proteoglycans, the main component of the nucleus pulposus 6) . This restricts the proteoglycans' water-holding capacity, reducing pressure inside the intervertebral disc, lowering the pressure on the nerve root from the hernia, and improving lower extremity and low back pain 6) . A previous study observed significant analgesic effects, improved lumbar function, and improved quality of life compared to a placebo in cases of protrusion-type or subligamentous-type lumbar disc herniation inside the spinal canal 7) .…”
mentioning
confidence: 99%